Antiretroviral activity from elderberry (Sambucus nigra L.) flowers against HIV-2 infection via reverse transcriptase inhibition: a viroinformatics study - Rahadian Zainul; Viol Dhea Kharisma; Pauline Ciuputri; Arif Nur Muhammad Ansori; Mochammad Aqilah Herdiansyah; Sukma Sahadewa; Fara Disa Durry (PAGEPress Publications, 2024)
HIV-2 infection is a unique concern with fewer cases than HIV-1, but it poses a high mortality rate due to its resistance to all HIV-1 antiretroviral treatments. This study focuses on one type of antiretroviral, reverse transcriptase (RT) inhibitors, as they play an important role in HIV-2 replication. The screening of potential HIV-2 antiretroviral candidates was carried out using compounds from elderberry (Sambucus nigra L.) flower extract. There is a lack of research on the antiviral potential of elderberry flower extracts, particularly in HIV-2; therefore, this study is important to explain the molecular mechanism underlying the potential of elderberry (Sambucus nigra L.) flower extracts to inhibit RT activity in HIV-2 through bioinformatics simulations. This study uses the in silico method, involving sample preparation in the database, drug-like molecular prediction through the server, molecular docking simulation, chemical bond interaction analysis, and three-dimensional structure visualization. Isorhamnetin has the most negative binding affinity of -9.9 kcal/mol compared to other compounds. It interacts with the HIV-2 RT domain at residues Trp4(B), Pro25(B), Asn137(B), Pro133(B), Gln23(B), Pro140(B), Leu21(B), Ile90(A), Thr131(B), Asn57(B), Arg22(B), and Glu89(A) with hydrophobic bond interactions. Hydrogen bond interactions are formed at the positions of Ser134(B), Gly141(B), and Thr88(A). Isorhamnetin from elderberry (Sambucus nigra L.) flower extract could be a potential HIV-2 antiretroviral candidate because it has the most negative binding affinity and the formation of hydrophobic hydrogen bond interactions on the RT domain.